Learning Arabic through OLA (Outdoor Learning Activity) Class VIII Junior High School in Sidoarjo Regency - Widya Khanif Fitriyanto; Imam Fauji (Universitas Muhammadiyah Sidoarjo, 2022)
This study aims to determine the preparation, implementation, evaluation and supporting and inhibiting factors of OLA (Outdoor Learning Activity) learning at SMP Muhammadiyah 1 Sidoarjo. This research is a narrative research using descriptive qualitative methods. The data collection techniques used were interviews, observations and documentation. The results of this study indicate that learning Arabic through OLA (outdoor learning activity) for class VIII students is very helpful in supporting the lack of learning hours in class and greatly affects the grades of class VIII students at SMP Muhammadiyah 1 Sidoarjo. .